Motoric development of stunting and nonstunting children on toddler - Susiani, Nonik; Muslihatun, Wafi Nur; Widyasih, Hesty (Jurnal Kesehatan Ibu dan Anak, 2019)
Stunting is associated with the increased risk of sickness and death, slow motoric development, and the delay of mental growth. Stunting can lead to delays in motoric systems development, whether in normal children or in people with a certain disease. The decreased motor function in stunting children without congenital abnormalities related to the low mechanical capability of triceps muscles due to the slow development of muscle function. This research was conducted to know the difference in motor development of stunting and non-stunting in toddlers in the service area of Sentolo I Public Health Centre (PHC), Kulon Progo. This research uses analytical methods of observational with Cross-Sectional Study design. The subjects of this study are 110 stunting and non-stunting children. The samples were taken with consecutive sampling techniques. Methods of data used questionnaires and direct measurement using the height measuring instruments and Denver II sheets. The analysis applies to the chi-squared test. The results show 71.7% of children with stunting in the suspect category on fine motor development, 60.4% of the children with stunting in the suspect category on gross motor development. The results of the statistical test show the score of p-value 0.016 for children in the suspect category on fine motor development and p-value 0.014 for children in the suspect category on gross motor development. The p-value score is < 0.05, meaning there is a significant difference in motoric development stunting and non-stunting children in the service area of Sentolo I PHC, Kulon Progo.